ANALISIS PELAPORAN KEUANGAN SEGMEN SEBAGAI ALTERNATIF INFORMASI PADA KEPUTUSAN INVESTOR DITINJAU DARI KESESUAIANNYA BERDASARKAN PSAK 5 PADA PT KIMIA FARMA TBK TAHUN 2019-2023 - Annisa Amalia; Ananda Dimas Aditya; Dina Sabina Fatmawati; Eka Cahaya Sukma; Anak Agung Ngurah Agung Adi Rama Putra Dalem; Wulandari Agustiningsih (Universitas Prof.Hazairin,SH Bengkulu, 2024)
This research aims to see the suitability of PT Kimia Farma Tbk segment reporting with PSAK No. 5 and the implications for financial statement users, particularly investors. Employing a qualitative descriptive method and utilizing secondary data from the 2019-2023 segment reports, the analysis was conducted in accordance with PSAK No. 5 and the ten percent significance technique to assess segment feasibility. The research findings indicate that PT Kimia Farma Tbk segment financial reporting adheres to PSAK No. 5 both qualitatively and quantitatively. The 10% threshold was applied to revenue, profit or loss, and assets. Total reported segment revenue reaches >75% of total revenue, so no additional segments are needed. PT Kimia Farma Tbk financial statements generally comply with PSAK No. 5. However, the company does not provide overall segment reconciliation and does not disclose geographic segments, as these do not align with its business processes. Segment reporting offers a clear view of a company performance, influencing investors decisions regarding fund allocation, management performance evaluation, and assessments of company transparency. This enables investors to make more informed and prudent investment decisions.